Lessons learned from low-cost athlete monitoring in lacrosse during a 12-week training cycle - Sisson, Olivia; Johnston, Camden; Noonan, Catherine; Bunn, Jennifer (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Monitoring athlete load is important for performance, but often includes expensive equipment. Aim of Study. The purpose of this study was to determine the feasibility of using heart rate (HR) monitors and session rating of perceived exertion (sRPE) to track training load for lacrosse athletes in practices and games and develop a load estimation during games. Material and Methods. Twelve Division I female lacrosse players wore chest straps and watches throughout 12-weeks of training sessions to measure cardiovascular load (CVL), and sRPE was collected after each session. Acute:chronic (A:C) training ratio was calculated using CVL and sRPE. Since athletes could not wear the HR monitor in regulated games, a multiplier was developed using HR data to estimate the CVL. Estimated CVL was compared to the actual CVL obtained during an exhibition game. Both sRPE and CVL were measured in arbitrary units (AU). Results. There was a moderate relationship between the CVL and sRPE load assessments (r = 0.445, p = 0.147). The mean A:C over the 12-week assessment period was 0.93 ± 0.17 AU and 1.13 ± 0.40 AU for CVL and sRPE load respectively, which is in the ideal range of A:C workload. The actual CVL (416.9 ± 100.6 AU) of an exhibition game compared poorly with CVL estimations using the game clock (227.2 ± 117.3 AU, r = 0.223, p = 0.565), running stopwatch (354.4 ± 145.7 AU, r = 0.195, p = 0.616), and running stopwatch excluding halftime (287.8 ± 147.0 AU, r = 0.195, p = 0.615). Conclusions. CVL and sRPE are feasible and cost-effective methods for monitoring training and A:C workload. CVL estimations for games were inaccurate, so sRPE should be used for low-cost game load assessment.
Keywords: session rating of perceived exertion; training load; workload; training impulse; monotony; strain